Who Is Writing About Women in STEM in Higher Education in the United States? A Citation Analysis of Gendered Authorship - Blackburn, Heidi; Heppler, Jason (Frontiers in Psychology, 2020)
The purpose of this study was to identify trends in the representation of female authorship regarding the topic of the status of women in science, technology, engineering, and math (STEM) in higher education in the United States from 2007-2018 in prominent interdisciplinary journals. We conducted a comprehensive search for articles and collected the genders of the first and senior authors from 647 citations. We assessed the number of male versus female authors, the percentages of female first authors and senior authors, and the percentage of female corresponding authors for each year. Additionally, we also analyzed the citations to determine the journals and publishers who produced the most literature in this area. Overall, women constituted 59% overall authorship and 34% first authorship. The top publishers in this area include Sage Publications, Springer/Nature, and Elsevier. Women constituted 60% of the first authors in STEM literature on the status of women and 38% of senior authors. Although there was growth over time in first authorship in STEM literature written by women, they continue to remain a minority in senior authorship. We suggest it is women that are leading this discussion, highlighting the additional lift that women in STEM in higher education must make; researching and publishing on their own experiences as part of their self-advocacy.